Islamic preaching on social media and its impact on religious attitudes: A bibliometric and systematic review of global research - Hurnawijaya; Sugian, Arif; Ihsan, Nafidul; Trimulyo, Agus; Abdillah; AL Kodri; Auladi, Akrom; Ihsanuddin, Muh; Cahyaristi, Nawangwulan; Rafsanjani, Akbar (Research Journal in Advanced Humanities, 2026)
This study examines the global development of scholarship on Islamic preaching (da’wah) on social media and synthesizes current knowledge regarding how digital religious communication relates to religious attitudes and orientations. It maps publication trends, influential contributors and regions, and dominant thematic directions in the field. Additionally, it explores how social media–based da’wah is associated with changes in personal religiosity, identity construction, and moral perspectives. A bibliometric and systematic review design was employed. Bibliometric data were retrieved from the Scopus database using structured search strings related to Islam and digital media. Following PRISMA procedures, 807 journal articles (2016–2026) were included in the bibliometric mapping, while 32 empirical studies met the inclusion criteria for the systematic review. VOSviewer and the Bibliometrix R package were used to analyze publication trends, influential contributors, country contributions, and thematic structures. The systematic review synthesized evidence regarding the impacts, mechanisms, and contextual moderators of digital da’wah. Research on Islamic preaching on social media has expanded rapidly, with strong contributions from Southeast Asia and increasing global participation. Instagram, YouTube, TikTok, and Facebook constitute the primary platforms for digital da’wah. The findings indicate that social media–based preaching can enhance personal religiosity, strengthen religious identity, and shape moral attitudes, including moderation and interfaith tolerance. However, it may also contribute to ideological fragmentation and polarization. These effects are mediated by exposure intensity, preacher credibility, and algorithmic amplification, and moderated by demographic, cultural, and platform-specific factors. This study provides an integrated mapping of the knowledge structure and empirical impacts of digital Islamic preaching by combining bibliometric analysis and systematic review methods. It offers a comprehensive framework for understanding how social media transforms religious attitudes, authority, and identity in contemporary Muslim societies.